2016
DOI: 10.1002/tox.22338
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fluoride on the structure, function, and proteome of a renal epithelial cell monolayer

Abstract: High concentrations of fluoride in the body may cause toxic effects. Here, we investigated the effects of fluoride on the structure, function, and proteome of a cortical collecting duct epithelium in vitro. Kidney tubule cells (M-1) were chosen because the concentration of fluoride in the kidney is 4-5-fold higher than that in plasma. Mouse M-1 cell monolayers were incubated in fluoride-containing media, and the amiloride-sensitive short-circuit current and transepithelial resistance were measured. The Young's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…The values of Young's modulus for control and fluoride‐treated cells were 12.9 ± 3.3 ( n = 4) and 21.0 ± 3.1; ( n = 4) kPa, respectively ( P = .12). Hence, fluoride treatment did not significantly affect the Young's modulus of the cells, as we reported recently for M‐1 mouse kidney cortical collecting duct epithelia . It is noteworthy that the Young's modulus of the Caco‐2 cell monolayer is substantially greater than the 1 kPa obtained for M‐1 cell monolayers, although it is similar to the value of about 25 kPa reported for MDCK cell monolayers …”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…The values of Young's modulus for control and fluoride‐treated cells were 12.9 ± 3.3 ( n = 4) and 21.0 ± 3.1; ( n = 4) kPa, respectively ( P = .12). Hence, fluoride treatment did not significantly affect the Young's modulus of the cells, as we reported recently for M‐1 mouse kidney cortical collecting duct epithelia . It is noteworthy that the Young's modulus of the Caco‐2 cell monolayer is substantially greater than the 1 kPa obtained for M‐1 cell monolayers, although it is similar to the value of about 25 kPa reported for MDCK cell monolayers …”
Section: Resultssupporting
confidence: 84%
“…In our experiments, fluoride reduced forskolin‐stimulated I sc and R t over identical concentration ranges (IC 50 , 3.1 mM). Hence, the Caco‐2 cell monolayers are considerably less sensitive to fluoride than M‐1 mouse kidney cortical collecting duct epithelia, in which both I sc and R t are reduced to zero at 1 mM fluoride (IC 50 , 300 μM). Although its molecular basis is unclear and the first insights into this aspect have only been recently reported, this difference might reflect the fact that the intestinal epithelium is the first barrier encountered by ingested fluoride.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In a recent study, the morphological alterations such as degeneration, necrosis of the tubular cells, renal tubular hyaline casts and swollen glomeruli abnormalities were detected in 12, 24, 48 mg/kg body weight NaF exposure mice after 42 days [27]. Interestingly, a previous study reported that, NaF could reduce the integrity of tight connections in M-1 cell monolayers of mice [28]. The impact of SO 2 changed the ultra-structural lesions in renal proximal tubular lining cells [22].…”
Section: Discussionmentioning
confidence: 99%
“…As we all know that F is necessary in lots of physiological activities. However, previous literatures have demonstrated that over-consumption of F not only damaged hard tissues, such as bone [3,4] and tooth [5,6], but also soft tissues, such as liver, kidney, thyroid, testis, uterus, and ovary [7][8][9][10][11]. Recently, literatures have suggested that over-intake F had intestinal toxicity [12,13], while the underlying mechanisms of the intestinal toxicity of F are unclear.…”
Section: Introductionmentioning
confidence: 99%